2023
DOI: 10.1002/ccr3.7085
|View full text |Cite
|
Sign up to set email alerts
|

A case of reversible hypoparathyroidism in a patient with Riedel's thyroiditis treated with glucocorticoids

Abstract: A 48‐year‐old woman with a history of primary hypothyroidism, presented with compressive symptoms secondary to a rapid enlargement of a preexisting goiter. She had no clinical signs of hypocalcemia. Biological tests revealed hypoparathyroidism. Cervicothoracic computed tomography scan showed a heterogeneous compressive goiter. The patient was treated with levothyroxine, calcium, and alfacalcidol. A total thyroidectomy was not performed because of the hard adhesion to neighboring structures. Histopathological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Since 2019, nine case reports of a single patient per paper have been published according to our methods [ 6 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since 2019, nine case reports of a single patient per paper have been published according to our methods [ 6 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…On admission, a patient (who is eventually confirmed with RT) may have a long history of multinodular goiter, Hashimoto’s thyroiditis (in terms of elevated serum positive antibodies against thyroid according to usual diagnosis in daily practice), or hypoechoic pattern at ultrasound with or without associated hypothyroidism and not being categorized as RT during this time period unless a sudden/progressive thyroid enlargement with compression effects emerges [ 6 , 44 ]. Gökçay Canpolat et al [ 52 ] reported that only 25% of their series had positive anti-thyroid antibodies, suggesting that not all individuals display serological confirmation of Hashimoto’s thyroiditis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations